Models for Type VI Adsorption Isotherms from a Statistical Mechanical Formulation - M. Ben Yahia; Y. Ben Torkia; S. Knani; M. A. Hachicha; M. Khalfaoui; A. Ben Lamine (Adsorption Science & Technology)
In this study, two theoretical expressions for the Type VI isotherm in the IUPAC classification are presented. The formulation of these new expressions is based on a rigorous statistical mechanical description. The expressions allow for the estimation of physicochemical parameters within the theoretical model. The proposed models allow a good correlation to Type VI experimental isotherms taken from the literature such as adsorption isotherms for adsorption of methane onto MgO (100) and onto an exfoliated graphite surface. The parameters intervening in the adsorption process have been deduced directly from experimental adsorption isotherms by numerical simulation. The theoretical expressions provide an understanding and interpretation of the adsorption isotherms at the microscopic level.